Cost-effective model of building construction based on GREENSHIP rating assessment using value engineering and lifecycle cost analysis methods - Sutikno Sutikno; Sarwono Hardjomuljadi; Henny Wiyanto (Discover Sustainability)
Abstract Regulation No. 21 of 2021, issued by the Minister of Public Works and Public Housing, mandates green building performance assessments for Building Approval (PBG) and Certificate of Functional Worthiness (SLF). However, many stakeholders perceive green building investments as costly. This study utilizes Soft Systems Methodology (SSM) to address these concerns and propose practical solutions. Through expert panel reviews, Content Validity Index, and structured questionnaires, five key variables were identified: conventional buildings (X1), green buildings (X2), value engineering (X3), life cycle cost analysis (X4), systematic risk (β), and cost performance (Y). These variables were divided into 26 dimensions and 92 indicators, leading to the development of a green building cost model. Structural Equation Modeling using SMART-PLS shows that life cycle cost analysis significantly impacts cost performance. Although initial investments in green buildings are higher, they account for a small proportion of total life cycle costs, making them financially viable in the long run. The model is represented as Y = 0.016X1 + 0.182X2 + 0.093X3 + 0.683X4 + β. The study introduces a cost-effective model integrating GREENSHIP, Value Engineering, and Life Cycle Cost Analysis, demonstrating the long-term financial advantages of green buildings. Practical recommendations are provided to enhance energy efficiency, productivity, and sustainability, aligning green building practices with financial and environmental goals for sustainable development.